Association of the 24-hour movement behaviours composition with workers’ chronic musculoskeletal pain - Aino Kitayama; Yu-Tai Liu; Ai Shibata; Sayaka Kurosawa; Koichiro Oka (PLoS ONE, 2026)
Background Chronic musculoskeletal pain is a significant symptom among workers. 24-hour movement behaviours comprising sleep, sedentary behaviour, light-intensity physical activity, and moderate-to-vigorous-intensity physical activity are associated factors. However, the relationships between these behaviours and workers’ chronic musculoskeletal pain, considering the interrelationship between the behaviours, are still unclear. This study aimed to investigate the associations of 24-hour movement behaviours with workers’ low-back and neck/shoulder pain. Methods In 2023, cross-sectional survey was conducted targeting adults who registered for a Japanese Internet survey system. Time for 24-hour movement behaviours and other demographic characteristics (age, gender, marital status, education, household income, height, weight, smoking, alcohol, chronic disease, work hours, and job activity) were self-reported. The intensity of low-back and neck/shoulder pain was evaluated using the numerical rating scale and a score of ≥4 was considered as moderate-to-severe pain. Compositional logistic regression and isotemporal substitution were performed to examine the associations of 24-hour movement behaviours and time reallocations between the behaviours with moderate-to-severe low-back and neck/shoulder pain, adjusted for all the demographic variables. Results 1,665 full-time workers (women: 35.8%, mean age: 42.1 ± 10.2 years) were analysed. Increased sleep and decreased light-intensity or moderate-to-vigorous-intensity physical activity were associated with lower odds of moderate-to-severe low-back (adjusted odds ratio [AOR] = 0.54, 95% confidence interval [CI] = 0.40–0.72; 1.45, 1.25–1.69; 1.17, 1.06–1.30, respectively) and neck/shoulder pain (AOR = 0.60, 95% CI = 0.45–0.80; 1.37, 1.19–1.60; 1.12, 1.01–1.24, respectively). Reallocating sleep from the other behaviours was associated with decreased probabilities of low-back and neck/shoulder pain, whereas replacing sedentary behaviour or light-intensity physical activity with more intense activity was associated with increased probabilities. However, the results of moderate-to-vigorous-intensity physical activity reallocation were no longer significant when restricted to complete cases. Conclusions Considering the interrelationship of 24-hour movement behaviours, sleep was favourably associated with workers’ low-back and neck/shoulder pain.